CONTRIBUTION OF ANIMAL AND PLANTS TO THE HUMAN SUSTAINABILITY IN THE LIGHT OF AL QURAN AS THEMATICAL APPROACH - RUSDI, MIKDAR; HAJI OMAR, MOHD AZMI (Human Sustainability Procedia, 2018)
Humans and other living creatures have never missed their need for animals and plants, without both ofthem life will no longer exist on earth. Hence, it contributes to life, of course, as a food supplier such as meat, rice, milk, eggs, vegetables and fruits, all of that for the survival process of mankind. From another point of view, animals and plants are created by Allah s.w.t.to preserve the continuation of the environment. These two creations of God play a crucial role in the preservation of the ecosystem on earth. Since the positions of the animals and plants are very significant by Allah s.w.t.thenthe Quran shows his serious concern to it by give the name of some chapters in the Quran with the names of animals or plants such as: surah al-Baqarah, al-Fil, al-Tin, al -An`am, al-Naml, al-Nahl and al-Ankabut. The naming of chapters of the Al Quran likethis is a sign that Islam very concerned about issues related to animals and plants. The findings of this paper will be found in the form of a brief review of the role of animals and plants in the Qur’an, its properties and functions in preserving human life